Binding of Anion to Ovotransferrin: Insight into pH Dependence of Binding Ability - Yang, Xiao-Jing (Asian Journal of Chemistry, 2012)
The binding of anions to ovotransferrin was studied by difference UV spectra. Direct titrations of ovotransferrin with phosphate, sulfate, pyrophosphate, citrate and monovalent anion chloride produce a strong negative absorbance near 237 nm and a weak negative absorbance near 280 nm. Presuming that each anion-binding site is identical, the calculation of the binding constants was carried out by the relevant equations. The anion-binding ability is pH-dependent.